Evaluasi Aplikasi E-Registration Modul Internet Versi 3.0 Menggunakan Indeks Kepuasan Pengguna Layanan Publik Berdasarkan Peraturan Menteri Pendayagunaan Aparatur Negara Dan Reformasi Birokrasi Nomor 14 Tahun 2017 - Vidya Indriyani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
Directorate General of Taxation develops E-Registration (E-Reg) related to the administrative process of taxpayer registration in order to carry out effective and efficient tax administration by utilizing information and communication technology. E-Reg is an application used to administer Taxpayer Identification Numbers (NPWP) and Taxable Entrepreneurs (PKP). The public service user satisfaction index based on the regulation of the Minister of Administrative Reform and Bureaucratic Reform Number 14 of 2017 concerning Guidelines for Satisfaction Surveys of Public Service Providers is used in order to evaluate the use of the internet version 3.0 E-Registration application by users. The Community Satisfaction Index is the measurement result of the Community satisfaction survey in the form of a number. Numbers are assigned a scale of 1 (one) to 4 (four). This study uses quantitative research methods to target respondents who represent the population of the research object. The questionnaire is designed to measure public service satisfaction. Respondent participation in this service user satisfaction survey involved 165,867 taxpayers with the minimum number of respondents required according to Krejcie & Morgan (1970) was 323 people. Processing of survey data using statistical data processing through validity and reliability tests. Questionnaire questions and index value measurements to measure the level of satisfaction of application users based on the average value of the questions. The index value is considered to represent the level of user satisfaction with a range of values between 1 to 5. The user satisfaction index value for the internet version 3.0 E-Registration application in this period is 4.656 on a scale of 5. The index results illustrate that the internet version 3.0 E-Registration application complies with user needs in providing NPWP registration services. However, there is still need for improvement and improvement in terms of application experience (UX) and application troubleshooting services so that they can be on par with other elements of user satisfaction. Keywords : E-Registration, User Satisfaction, Public Service